Angiotensin II Modulates Podocyte Glucose Transport - Lewko, Barbara; Maryn, Anna; Latawiec, Elzbieta; Daca, Agnieszka; Rybczynska, Apolonia (Frontiers in Endocrinology, 2018)
Podocytes play a central role in the maintenance of the glomerular filtration barrier and are cellular targets of angiotensin II (AngII). Non-hemodynamic pathways of AngII signaling regulate cellular function and mediate podocyte abnormalities that are associated with various glomerulopathies, including diabetic kidney disease. In this study we investigated the capacity of AngII to modulate glucose uptake in mouse podocytes expressing the human AT1 receptor (AT1R+) after 5 days of exposure to normal (NG, 5.6 mmol/L) or to high (HG, 30 mmol/L) glucose. Short (30 min) as well as long-term (24 h) incubations with AngII markedly enhanced glucose transport in both NG and HG cells. In podocytes cultured under NG conditions, AngII inhibited insulin-stimulated glucose uptake. Regardless of the presence or absence of AngII, no effect of insulin on glucose uptake was observed in HG cells. Stimulation of glucose transport by AngII was mediated by protein kinase C and by phosphoinositide 3-kinase. Glucose dependent surface expression of the glucose transporters GLUT1, GLUT2, and GLUT4 was modulated by AngII in a time and glucose concentration dependent manner. Furthermore, despite its inhibitory effect on insulin's action, AngII elevated the number of podocyte insulin receptors in both NG and HG cultured cells. These findings demonstrate that AngII modulates podocyte basal, as well as insulin-dependent glucose uptake by regulating glucose transporters and insulin signaling.